MASKULINISASI IKAN CUPANG (Betta splendens) MENGGUNAKAN MADU ALAMI MELALUI METODE PERENDAMAN - Annisa Siregar; Mochamad Syaifudin; Marini Wijayanti (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACT This research aims to determine the effect of natural  honey to male percentage of betta fish by masculinization. This researchwas conducted at FisheriesBasic Laboratory,  Faculty of Agriculture, Sriwijaya University on January– February 2018. This research  usedcompletely randomized design (CRD) with 5 treatments and 3 replications. The treatment in this research was4 day of betta fish larvae  that submersed in 5 ml/L  natural honey with different immersiontime.The treatmentconsisted of P0 (without natural honey), P1 (12 hours of immersion), P2 (16 hours of immersion), P3 (20 hours of immersion),and P4 (24 hours of immersion). The observed parameters were post-immersion survival percentage, percentage of male betta fish, post- rearing survival percentage and water quality. The result showed the percentage of male betta fish was 47,50 % (P0), 66,35 % (P1), 73,51% (P2), 75,37 (P3), and 85,14 % (P4). Water quality during maintenace were temperature 27,4-28,8 oC, pH 5,3-5,8, DO 3,43-3,59 mg/L and amonia 0’001-0,002 mg/L. Treatment of P4 (24 hours of immersion) indicatedthe best treatment with larval survival percentage andmale percentage were 90.00% and 85.14% respectirely. Keywords : Betta fish (Betta splendens), masculinization,natural honey